Güncel Çocuk Sağlığı ve Hastalıkları VII (Bahar) - Özgökçe Özmen, Berfin; Vardar, Gonca; Say, Aysu; Belder, Nuran; Kayalı, Şeyma; Güneş, Ömer; Gürel, Selçuk; Leblebici, Ayben; Duman, Derya; Uslu, Gonca; Malbora, Barış (2024)
-